PENGARUH MEDIA BOLA BASKET TERHADAP KETERAMPILAN PASSING ATAS PADA EKSTRAKURIKULER BOLA VOLI DI SMAN 1 SINDANG - Prasetyo, Aldian; Sumarsono, Rhama Nurwansyah; Purbangkara, Tedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Many members of the volleyball extracurricular at SMAN 1 Sindang, both the men's team and the women's team, do not master the basic top passing techniques. The aim of this research is to find out whether basketball media influences top passing skills in volleyball extracurriculars at SMAN 1 Sindang. This research uses a quantitative approach with experimental research methods. The sample in this study was all members of the volleyball extracurricular at SMAN 1 Sindang, totaling 22 people with the sampling technique used, namely using a total sampling technique. The form of research design used is a pre-experimental design with a one-group pretest-posttest design. The instrument used in this research was the Upper Passing Test (AAHPER face wall-volley test). Data analysis used the SPSS version 26 application. The results of the study showed that there was a significant influence which could be seen in the average results before treatment (treatment) and after treatment (treatment) which experienced a significant increase, namely the pretest mean of 43.18 to the posttest mean of 60. 00. Meanwhile, the calculation results of the Paired Sample T Test hypothesis test with the data obtained from this research is a sig (2-tailed) value of 0.000 < 0.05, meaning that there is a significant influence between the average value before treatment and the average value before treatment. average value after treatment. It can be concluded that basketball media can influence top passing skills in volleyball extracurriculars at SMAN 1 Sindang.